Efektivitas Kebijakan Online Single Submission pada Dinas Penanaman Modal Pelayanan Terpadu Satu Pintu Tangerang Selatan - Nazwa Nurfauziah; Mawar Mawar; Fal Harmonis; M Qudrat Nugraha (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Licensing is an important factor for investors when making an investment. To speed up and simplify the licensing process, the government created the Online Single Submission (OSS) system. In South Tangerang, the Department of Investment and One Stop Integrated Services (DPMPTSP) plays an important role in the coffee shop business licensing process. To open a coffee shop, a location permit, environmental permit, NIB and business trading permit through OSS are required. Obstacles in the licensing process often cause delays and difficulties for business actors. The aim of this research is to determine and analyze the effectiveness of applying for coffee shop business permits through Online Single Submission at the South Tangerang One Stop Integrated Services Investment Service. The method used in the research is a qualitative approach with descriptive research type. This research uses the theory of Thomas R. Dye (2013). The research results show that the indicators for setting clear goals have not been achieved optimally even though the goals of time efficiency and transparency of business permits through the OSS system are quite effective. In the results measurement indicators, positive results have been achieved, which can be seen from the success of OSS in increasing the number of NIBs by 10% from the previous year. Performance evaluation indicators are not optimal due to limited email, network and server constraints, apart from that the appearance and provisions of the OSS system also make it difficult for users to access the OSS system again. In the cost-benefit analysis indicator, it is quite efficient in reducing permit processing time and without any costs incurred. Contextual factor indicators provide a positive impact where the JOSS Program is a form of the South Tangerang government's commitment to assisting the community in licensing through the OSS system. The feedback and adjustment indicators have not been optimal in providing guidance and information to business actors, so there are still business actors who have not registered their business permits through this OSS system.